Does gratitude writing improve the mental health of psychotherapy clients? Evidence from a randomized controlled trial. (4th March 2018) - Wong, Y. Joel; Owen, Jesse; Gabana, Nicole T.; Brown, Joshua W.; McInnis, Sydney; Toth, Paul; Gilman, Lynn
Abstract: Although the past decade has witnessed growing research interest in positive psychological interventions (PPIs), their potential as adjunctive interventions for psychotherapy remains relatively unexplored. Therefore, this article expands the frontiers of PPI research by reporting the first randomized controlled trial to test a gratitude writing adjunctive intervention for psychotherapy clients. Participants were 293 adults seeking university-based psychotherapy services. Participants were randomly assigned to one of three conditions: (a) control (psychotherapy only), (b) a psychotherapy plus expressive writing, and (c) a psychotherapy plus gratitude writing. Participants in the gratitude condition wrote letters expressing gratitude to others, whereas those in the expressive writing condition wrote about their deepest thoughts and feelings about stressful experiences. About 4 weeks as well as 12 weeks after the conclusion of the writing intervention, participants in the gratitude condition reported significantly better mental health than those in the expressive and control conditions, whereas those in the expressive and control conditions did not differ significantly. Moreover, lower proportions of negative emotion words in participants' writing mediated the positive effect of condition (gratitude versus expressive writing) on mental health. These findings are discussed in light of the use of gratitude interventions as adjunctive interventions for psychotherapy clients.